A Rare Presentation of Hiccups Caused by Lung Abscess: A Case Report - Raj, Amal; Chathambath, Anjana; Baby, Bilha; Subramaniam, Sobha; Waghray, Kunal; Ajith, Goutham Seema; Joy, Selin C (Indian Journal of Pharmacy Practice)
Background: A lung abscess is a pus-filled microbial infection of the lung that results in necrosis of the pulmonary parenchyma, which may compress the vagal and phrenic nerves, leading to hiccups. Hiccups are usually harmless and self-limiting. They can become persistent if they last longer than 48 hr and they can become intractable if they last longer than two months. Despite the various non-medical conditions; metabolic issues, central nervous tissue disorders and nerve damage contribute to the etiology of hiccups. Aim: Several case reports suggest that vagus nerve irritation can lead to various cardiac, pulmonary and digestive problems. We aim to report a unique case of hiccups induced by phrenic nerve irritation caused by lung abscess. Clinical Details: A 59-year-old male patient who presented with right-sided chest pain and persistent hiccups induced by lung abscess for 4 days. The patient had a prior history of sputum-positive pulmonary Tuberculosis (treated and cured in 2002). Outcomes: The patient was managed with IV antibiotics and Tablet Baclofen and was discharged once the patient was stable. Conclusion: The unusual presentation of hiccups induced by phrenic nerve irritation has been less noted in clinical practice. This case report gives a thorough picture of the problems brought on by compression of the phrenic nerve due to a lung abscess.
Keywords: Lung abscess; Hiccups; Intractable; Vagus nerve irritation